Catalytic amination of lactic acid using Ru–zeolites. Issue 28 (5th May 2022) - Shah, Meera A.; Khalil, Ibrahim; Tallarico, Sofia; Donckels, T.; Eloy, Pierre; Debecker, Damien P.; Oliverio, Manuela; Dusselier, Michiel
Abstract : Ru supported on zeolite catalysts: a case study for the direct amination of biobased alpha-hydroxy acids into alpha-amino acids. Abstract : In this work we investigate the synthesis of alanine from lactic acid, a biobased platform chemical, using ammonia as a nitrogen source and Ru/zeolite catalysts. We report a high alanine selectivity when using Ru/BEA of 80–93%. Reaction side products were identified as ethanol, propionic acid or propanamide and the reaction mechanism was investigated. We further optimised reaction conditions resulting in turn over numbers five times higher than previously reported and could reduce Ru leaching by 30–40%. However, leaching and catalyst stability remains a concern. Furthermore, we critically analyse the benefits of Ru/zeolites versus their stability under the basic, high temperature reaction conditions.